PEREMPUAN BEKERJA SEBAGAI SATUAN PENGAMAN (SATPAM) DI RUMAH SAKIT SANTA MARIA KOTA PEKANBARU - Sri Ayu Wulandari; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was coducted at the security women in the hospital Santa Maria does the Pekanbaru city. The purpose of this research is to know the reason for the women in choosing a job as units safety (security) and obstructios faced while working. The subject of the study amounted to 7 people of the security women. The technique of determinations of informants by using purposive technique of sampling. Data sources used are primary and secondary data sources.The author uses qualitative descriptive method and instrument data is observations, interview and documentation. The result of the research obtained, the main reason that makes women choose to work as a security is economic problems, because the salaries that they receive are quite large and metches the UMK (Upah Minimum Kota). For the women security who are married, they want to help to increase the income of their husband because if only their husband’s who work, then their family’s needs are less meet. For the women security who are single/unmarried, they choose to work as a security guard because they have to meet their needs, to live independently ada away from parents. Another reason that makes women choose to work as a security guard because they love the job and also the suport of family and outsiders, and the presence af the opportunity given by certain parties who want to use the services of female security, for exsample Santa Maria Hospital. Barrier exsperienced by femele security at work come from the outside. from visitors who don’t want to follow the rules of Santa Maria Hospital. Sometime the visitors are hard and bawl. The ways to resolve these barrier is explain the rules kindly and friendly, because theirs job is to provide service.Keywords: Choosing, Work, Female security guards